(3QSGdI aj CNHGQ Hf GdSjO GdHWdjhSis - (3GHf NGbGf , CHh fUQ,J (B528 (3g` s
(3ChdgG (B:s
(3CeG HYO MeO Gddg GdPi LYd Gddjd dHGSkG hCRGd Yf bdhHfG TckG h EdJHGSkG aQCjJ Cf CSJNQL ef CNHGQg NHQkG jOd Ydjg OdGdI GddaX Ydi GdeYfi s
(3BNQgG (B:s
(3CeG JQi GdfaS cGdTeGFd hGZaQ PfhHi s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B1s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B134 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B49s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3MGdI GdfSNI SjFI s
Keywords: (3GdJGQjNs